2015
DOI: 10.1155/2015/504208
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of MicroRNAs in Peripheral Blood Mononuclear Cells: As Novel Biomarkers of Ankylosing Spondylitis and Provocative Therapeutic Targets

Abstract: Background. MicroRNAs can potentially regulate every aspect of cellular activity. In this study, we investigated whether AS pathogenesis involves microRNAs disorders. Result. The expression of 2 microRNAs, hsa-miR-126-3p and hsa-miR-29a, was significantly lower in active AS group before etanercept therapy than in control group. Marched fold changes of them were 3.76 and 16.22. Moreover, expressions of hsa-miR-126-3p and hsa-miR-29a were dramatically upregulated after 12-weeks etanercept treatment. Fold changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…MiR‐27a and miR‐126‐3p, which have been previously reported as aberrantly expressed in patients with AS, were also verified upregulated in patients with nr‐axSpA rather than in healthy controls in our study. The relative expression of miR‐27a in patients with nr‐axSpA was slightly higher than in patients with AS, while miR‐126‐3p was expressed similar in both patients with nr‐axSpA and AS.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…MiR‐27a and miR‐126‐3p, which have been previously reported as aberrantly expressed in patients with AS, were also verified upregulated in patients with nr‐axSpA rather than in healthy controls in our study. The relative expression of miR‐27a in patients with nr‐axSpA was slightly higher than in patients with AS, while miR‐126‐3p was expressed similar in both patients with nr‐axSpA and AS.…”
Section: Discussionsupporting
confidence: 83%
“…On the basis of a previous study on microarray results, as well as verification experiments, miR‐17‐5p, miR‐27a, miR‐29a and miR‐126‐3p have been seen to be dysregulated in patients with AS. Thus, these four miRNAs were selected for further research.…”
Section: Introductionmentioning
confidence: 92%
“…Studies have shown the association between miR-29a-3p and ankylosing spondylitis (AS) [28,29]. Although data on miR-29a-3p levels in AS are inconsistent, Prajzlerova et al reported that patients with advanced-stage AS with extensive bone formation have higher levels of TGF-β, as well as miR-29a suppression and increased bone formation [30].…”
Section: Discussionmentioning
confidence: 99%
“…The data on miR-29a levels in AS are rather inconsistent. While miR-29a expression in peripheral blood mononuclear cells was lower in active AS patients than in controls and decreased after anti-TNF therapy [ 32 ], another showed otherwise [ 33 ]. TGF-β, an important stimulator of bone formation [ 34 ], inhibits miR-29a expression [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%